Tinjauan Yuridis Mengenai Perwalian Anak Yatim Piatu yang Masih dibawah Umur - Eva Cahyana Dewi (Perspektif Hukum, 2020)
Marriage is a sacred and important legal event in human life. A marriage that is a bond between two individuals can have various legal consequences. Marriage will have legal consequences for both husband and wife, property and children born in the marriage. One of the legal consequences of being born from a marriage is the acquisition of the right to inherit from a child from both parents. However, there are times when a husband and wife have passed away leaving an heir who is not old enough so that the child does not have parents as guardians or so-called orphans. The formulation of the problem taken by the author is the legal consequences of the marriage related to the right to bequeath a child. And the guardianship of orphans in the legal system in Indonesia. This study used normative legal research that is prescriptive in nature. The sources of legal materials in this study are primary and secondary data. As for the collection of data, this study used literature study techniques with a statutory and conceptual approach. Based on the results of the study, the authors obtained answers to the problem, namely a marriage is a legal act that will cause legal consequences to both the husband and wife, property and children born in marriage. In marriage, it is possible for the death of both husband and wife to result in the inheritance of their child. However, since in this case both parents of the child are gone, this agreement cannot be made. Generally, the appointment of a guardian will be based on the contents of the will of the parents. However, if the child does not have a will, then whoever is a relative or other person who wants to become a guardian, needs to submit an application for a ruling to the local Religious Court or District Court.